(untitled) (Technical Journal, 2025)
This research investigates factors contributing to extended construction cycle times in tunnel projects within the geologically challenging Siwaliks region of the Nepal Himalaya, characterized by interbedded sandstone and mudstone. Focusing on the 1126 meters long Siddhababa Tunnel with 110 square meters cross sectional area constructed using the conventional Drill and Blast Method, the study analyzes the impact of local geology on construction efficiency. Findings indicate that weak rock classes, specifically MS-IV-A, significantly increase the construction cycle time, demanding careful management of dummy holes and explosives. The paper then contrasts these practices with the NTNU model, highlighting its superior efficiency. The NTNU model offers advantages primarily because it utilizes drilling jumbos instead of manual drilling, a single ventilation phase per cycle compared to dual requirement for heading and benching, and increased mucking efficiency due to larger truck sizes. The study concludes that adopting NTNU methods offers a significant potential to reduce cycle times and improve overall tunneling efficiency for future projects undertaken in similar geological conditions and construction practices.